Recommendation for Reconstructing Green HRM Indicators Through Tawhidi Methodology - Sofyan, Riyanto; Hubur, Aa; Soeharjoto, Soeharjoto (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
The transition toward sustainable tourism relies on effective Green Human Resource Management (GHRM). However, conventional GHRM frameworks utilize an anthropocentric and secular paradigm that frequently fails to foster long-term ecological commitment. This limitation is evidenced by the empirical failure of material-based green rewards to drive pro-environmental behavior among employees. To address this profound motivational gap, this conceptual paper theoretically reconstructs conventional GHRM indicators within the tourism industry by integrating the Tawhidi Methodological Worldview (TMW). Employing directed qualitative content analysis, this study conducts a theoretical critique of existing empirical GHRM definitions. By mapping secular indicators against Maqasid al-Shari’ah principles and the Maslahah hierarchy, findings reveal fundamental ontological flaws that reduce ecological responsibility to mere corporate cost-efficiency. Repositioning green practices from voluntary actions into absolute institutional obligations, this study formulates novel Tawhidi-based GHRM indicators. These reconstructed metrics organically inject theological concepts, namely Amanah (divine trust), Tazkiyah (purification), Muhasabah (self-introspection), Falah (holistic well-being), and Nafs al-Muthmainnah (tranquil soul), into core human resource dimensions. Ultimately, integrating Tawhidi values bridges the existing professional-spiritual dichotomy, offering an adaptive framework for Muslim-friendly tourism driven by transcendental motivation.